Ease the queue oscillation: analysis and enhancement of DCTCP - Chen, Wen; Cheng, Peng; Ren, Fengyuan; Shu, Ran; Lin, Chuang (ICDCS, 2013)
Because of the terrible performance of TCP protocol in data center environment, DCTCP has been proposed as a TCP replacement, which uses a simple marking mechanism at switches and a few amendments at end hosts to adjust congestion window based on the extent of the congestion in networks. Thus, DCTCP can make a proper tradeoff between high throughput and low latency. However, through our observation, we discover that DCTCP causes severe oscillation of queue under some parameters and network configuration. Our perceptual analysis concludes that the rough single-threshold marking mechanism may be the essential reason. Therefore, we propose Double-Threshold DCTCP as an improvement of DCTCP. Then, by applying describing function method in nonlinear control theory, we analyze the stability of both DCTCP and Double-Threshold DCTCP, and theoretically explain why Double-Threshold DCTCP is more stable than DCTCP. At last, we validate theoretical analysis and conclude that the Double- Threshold DCTCP can achieve smaller queue, and the queue length of Double-Threshold DCTCP is less sensitive to the growing number of flows. Further, Double-Threshold DCTCP can postpone the throughput collapse caused by Incast traffic and reduce the tail latency in completion time experiment.